Vacuum high-wear-resistance zirconia-based composite ceramic material as well as preparation method and application thereof

By introducing toughened whiskers and vacuum carburizing technology into zirconia ceramics, vacuum high-wear resistant zirconia matrix composite ceramics are prepared, which solves the problem of deterioration of wear performance of zirconia ceramics in vacuum environments, and has achieved significantly improved wear resistance and self-lubricating performance. It is suitable for high-end equipment components in the aerospace field.

CN119504277AActive Publication Date: 2025-02-25XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202411656575.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

Zirconia ceramics have significantly deteriorated wear performance in vacuum or high vacuum environments, which cannot meet the needs of reliable and long-lasting service for high-end aerospace equipment.

Method used

A combination of toughened whiskers and vacuum carburizing technology is used to prepare vacuum high-wear zirconia-based composite ceramic materials. Specific steps include mixing zirconia powder, stabilizer and anhydrous ethanol, adding whiskers and drying and sieving, followed by static pressure forming, vacuum sintering and annealing, and finally high-temperature carburizing and surface treatment.

Benefits of technology

It significantly improves the tribological properties of zirconia-based ceramics in vacuum environments, improves wear resistance, reduces the dry friction coefficient, and meets the long-life and reliable service needs of high-end equipment components in the aerospace field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504277A_ABST
    Figure CN119504277A_ABST
Patent Text Reader

Abstract

The invention discloses a vacuum high-wear-resistance zirconia-based composite ceramic material as well as a preparation method and application thereof, and belongs to the technical field of ceramic material preparation. The preparation method comprises the following steps: 1) sufficiently and uniformly mixing zirconium oxide powder, a stabilizer and absolute ethyl alcohol to prepare mixed slurry; 2) adding whiskers into the mixed slurry, fully and uniformly stirring, and then drying and sieving to obtain mixed powder; 3) carrying out static pressure molding on the mixed powder to prepare a composite ceramic biscuit, and then carrying out vacuum sintering and annealing treatment to prepare composite ceramic; and 4) performing high-temperature carburizing treatment on the composite ceramic to obtain carburized composite ceramic, and performing surface treatment to obtain the vacuum high-wear-resistance zirconia-based composite ceramic material. The vacuum wear rate of the zirconia-based composite ceramic material provided by the invention is reduced by 1-2 orders of magnitude compared with that of a traditional yttria-stabilized zirconia material, and a novel high-wear-resistance ceramic material is provided for precise friction driving parts in the field of aerospace.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic material preparation, and specifically relates to a vacuum high-wear-resistant zirconia-based composite ceramic material and a preparation method and application thereof. Background Art

[0002] Zirconia (ZrO2) ceramics have attracted widespread attention because they have the advantages of traditional ceramic materials such as mechanics, high temperature resistance, corrosion resistance, insulation, and excellent fracture toughness. At present, zirconia-based ceramics have been successfully used in biomedicine, aerospace, electronic information and other fields as wear-resistant and corrosion-resistant materials, thermal insulation / heat-resistant materials, and dielectric materials. With the rapid development of aerospace technology, higher requirements are also placed on the service performance of wear-resistant materials under harsh working conditions such as high vacuum and high load. However, the wear resistance of zirconia self-matching pairs is significantly degraded in vacuum or high vacuum, and its high wear rate cannot meet the needs of reliable and long-life service of high-end aerospace equipment.

[0003] Research on zirconia mainly focuses on the regulation of material composition and microstructure to improve its toughness, but there are few studies on improving its vacuum / high vacuum wear resistance. Studies have shown that the introduction of suitable whiskers can enhance the toughness and mechanical properties of zirconia ceramics, but its effect on the high vacuum friction and wear performance of zirconia remains to be explored. Carburizing is an effective method to regulate the surface properties of materials. Related studies have shown that after carburizing treatment, carbon mainly exists in the lattice gap of zirconia in the form of atoms, which is beneficial to reduce its friction coefficient. Patent applications with publication number CN1108229A "A method for carburizing oxide ceramics" and patent applications with publication number CN103724051A "Carburizing method for ceramic sliding materials" respectively proposed methods for carburizing oxide ceramics, but did not involve research on the vacuum tribological properties of zirconia ceramic materials. In addition, a single carburizing treatment may lead to a decrease in the fracture toughness of zirconia ceramics, which is not conducive to improving its wear resistance.

[0004] In summary, the obvious degradation of zirconia wear performance in vacuum or high vacuum environment seriously restricts its wide application in the aerospace field. Therefore, a vacuum high wear-resistant zirconia-based ceramic material and its preparation method are proposed, which is of great significance for the long-life and reliable service of friction parts of high-end aerospace equipment. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a vacuum high-wear-resistant zirconia-based composite ceramic material and its preparation method and application, so as to solve the technical problem that the single carburizing treatment in the prior art leads to low fracture toughness and poor wear resistance of zirconia ceramics.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing a vacuum high-wear-resistant zirconium oxide-based composite ceramic material, comprising the following steps: 1) Fully mix zirconium oxide powder, stabilizer and anhydrous ethanol to prepare a mixed slurry; 2) Add whiskers to the mixed slurry, stir thoroughly, and then dry and sieve to obtain a mixed powder; 3) The mixed powder is statically pressed to obtain a composite ceramic green body, and then vacuum sintered and annealed to obtain a composite ceramic; 4) Carburizing the composite ceramic at high temperature to obtain carburized composite ceramic, and then subjecting the composite ceramic to surface treatment to obtain a vacuum high wear-resistant zirconia-based composite ceramic material.

[0007] Preferably, in step 1), the amount of the stabilizer is 1.5% to 5% of the amount of zirconium oxide powder; and the volume ratio of the total powder of zirconium oxide powder and stabilizer to anhydrous ethanol is 1 to 1.5:1.

[0008] Preferably, the stabilizer is one or more of yttrium oxide, magnesium oxide and calcium oxide.

[0009] Preferably, high-purity zirconium oxide powder, a stabilizer, and anhydrous ethanol are mixed and ball-milled, and filtered to obtain a mixed slurry; Further preferably, the grinding jar and grinding balls used in the ball mill are both made of zirconia, the ball mill speed is 150 r / min~300 r / min, and the duration is 6 h~15 h.

[0010] Preferably, in step 2), the amount of whiskers used accounts for 5% to 20% of the mass of the mixed slurry; the whiskers are one or more of silicon carbide, silicon nitride, aluminum oxide and magnesium oxide.

[0011] Preferably, the sieving in step 2) uses a 100-300 mesh sieve.

[0012] Preferably, in step 3), the static pressing pressure is 150 MPa-300 MPa, and the holding time is 10 min-30 min; the process parameters of vacuum sintering and annealing treatment are: starting from room temperature, heating to 1200°C-1500°C at a temperature rise rate of 3-10°C / min, holding time 2 h-10 h, and then cooling to room temperature with the furnace.

[0013] Preferably, in step 4), a vacuum carburizing furnace is used for high-temperature carburizing treatment, and the process parameters of the high-temperature carburizing treatment are: the carburizing medium is one or more of methane, ethane, acetylene and ethylene, the temperature is increased from room temperature to 850°C~1450°C at a temperature rise rate of 3~10°C / min, the carburizing time is 8h~24h, and the cavity pressure is 1~20 Kpa.

[0014] Preferably, in step 5), the surface treatment is performed by grinding and polishing with 600 mesh, 1200 mesh, 2000 mesh and 3000 mesh sandpaper in sequence until the surface roughness is less than 0.1 μm.

[0015] The present invention also discloses a vacuum high wear-resistant zirconia-based composite ceramic material prepared by the above-mentioned preparation method, wherein the vacuum high wear-resistant zirconia-based composite ceramic material contains a carburized layer inside and is distributed with whiskers as a toughening phase; wherein the thickness of the carburized layer with a carbon content higher than 0.75% is greater than 10 μm; the length of the whiskers is 5 μm to 150 μm, and the aspect ratio is greater than 5.

[0016] Preferably, the composite ceramic material contains 70 wt% to 90 wt% of zirconium oxide, 5 wt% to 20 wt% of reinforcing phase whiskers, and a stabilizer content of 2 mol% to 5 mol% of the zirconium oxide.

[0017] Preferably, the dry friction wear rate of the vacuum high wear-resistant zirconia-based composite ceramic material in a vacuum environment is 10 -7 ~10 -8 mm 3 / N·m order of magnitude.

[0018] Preferably, the surface of the material is uniformly gray-black.

[0019] The present invention also discloses the application of the above-mentioned vacuum high wear-resistant zirconia-based composite ceramic material in the field of aerospace high-end equipment manufacturing.

[0020] Preferably, it is used to prepare key components such as anti-wear and friction drive; More preferably, it is used for preparing high-performance actuators, etc.

[0021] Compared with the prior art, the present invention has the following beneficial effects: The method for preparing a vacuum high-wear-resistant zirconia-based composite ceramic material disclosed in the present invention introduces toughening whiskers into a stable zirconia ceramic matrix, and uses vacuum carburizing technology to infiltrate carbon atoms with a wear-reducing effect into the ceramic surface, so as to synergistically improve the mechanical properties and vacuum self-lubricating properties of traditional zirconia ceramics, and significantly improve the tribological properties of zirconia-based ceramics in a vacuum environment, thereby effectively solving the technical problem that the single carburizing treatment in the prior art leads to low fracture toughness and poor wear resistance of zirconia ceramics. At the same time, the preparation method is easy to control the component content, simple to operate, and has a high yield. The zirconia-based composite ceramic material prepared by the present invention has great application potential in the field of high-end equipment in the aerospace field.

[0022] The zirconia composite ceramic material prepared by the present invention has a certain self-lubricating property in a vacuum environment, and the wear rate is increased by 1 to 2 orders of magnitude compared with the traditional yttria or magnesium oxide stabilized zirconia ceramic material, and its dry friction coefficient is reduced by more than 20%. Therefore, it can be applied to the aerospace field, providing a new type of highly wear-resistant composite ceramic material for high-end equipment components in the aerospace field. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the structure of the vacuum high wear-resistant zirconia-based composite ceramic material disclosed in the present invention; Figure 2 The figures are the physical pictures of Example 1 and Comparative Example 1; Figure 3 The nanohardness of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 of the present invention; Figure 4 It is the average wear rate of Example 1 of the present invention, Example 1 of the present invention, Comparative Example 1 and Comparative Example 2 in a vacuum environment. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0025] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0026] The present invention is further described in detail below in conjunction with the accompanying drawings: Example 1 In this embodiment, yttrium oxide is used as a stabilizer, silicon carbide whiskers and vacuum carburization are used to prepare zirconium oxide-based composite ceramics, and the total mass of the powder (the total mass of the stabilizer, whiskers, zirconium oxide and binder) is used as a benchmark. The specific implementation includes the following steps: 1) Yttria-stabilized zirconia slurry 80 wt% of zirconium oxide powder, yttrium oxide stabilizer and anhydrous ethanol were added into a zirconium oxide ball mill, wherein the amount of yttrium oxide added was 3 mol% of zirconium oxide, the volume ratio of anhydrous ethanol to powder was 1-1.5, the ball mill speed was 200 r / min, the ball milling time was 10 h, and the grinding balls were filtered out to obtain a mixed slurry; 2) Composite powder preparation 10 wt% silicon carbide whiskers and 0.75 wt% binder (PVB) were added to the mixed slurry, and the mixture was stirred for 90 min; the mixed slurry was then dried and sieved (mesh size 200) to obtain silicon carbide whisker reinforced zirconia composite powder; 3) Composite ceramic blank The composite powder was placed in a mold and kept at a static pressure of 300 MPa for 20 min to obtain a composite ceramic green body; 4) Composite ceramic firing The composite ceramic green body was placed in a vacuum sintering furnace, the furnace temperature was raised to 1450°C at a rate of 5°C / min, and after being kept at this temperature for 2.5 hours, it was naturally cooled to room temperature to obtain a composite ceramic; 5) Carburizing The composite ceramic was placed in a vacuum carburizing furnace, heated to 900 °C at a rate of 5 °C / min, introduced with acetylene gas and a vacuum degree of 2 KPa, maintained for 20 h, and then naturally cooled to room temperature to obtain a carburized composite ceramic. 6) Grinding and polishing The carburized composite ceramics were ground with 600 mesh, 1200 mesh, 2000 mesh and 3000 mesh sandpaper in turn to remove the surface carbon layer, and finally polished until the surface roughness was less than 0.1 μm, thus completing the material preparation.

[0027] Example 2 In this embodiment, yttrium oxide is used as a stabilizer, silicon nitride whiskers and vacuum carburization are used to prepare zirconium oxide-based composite ceramics, with the total mass of the powder as the reference. The specific implementation includes the following steps: 1) Yttria-stabilized zirconia slurry 75 wt% of zirconium oxide powder, yttrium oxide stabilizer and anhydrous ethanol were added into a zirconium oxide ball mill, wherein the amount of yttrium oxide added was 4 mol% of zirconium oxide, the volume ratio of anhydrous ethanol to powder was 1-1.5, the ball mill speed was 150 r / min, the ball milling time was 12 h, and the grinding balls were filtered out to obtain a mixed slurry; 2) Composite powder preparation 12 wt% silicon nitride whiskers were added to the mixed slurry, and the mixture was stirred for 120 min; the mixed slurry was then dried and sieved (mesh size 200) to obtain silicon nitride whisker reinforced zirconia composite powder; 3) Composite ceramic blank The composite powder was placed in a mold and kept at a static pressure of 200 MPa for 25 min to obtain a composite ceramic green body; (the binder used for granulation is polyethylene glycol and polyvinyl alcohol) 4) Composite ceramic firing The composite ceramic green body was placed in a vacuum sintering furnace, the furnace temperature was raised to 1400°C at a rate of 5°C / min, and then naturally cooled to room temperature after being kept at this temperature for 5 hours to obtain a composite ceramic. 5) Carburizing The composite ceramic was placed in a vacuum carburizing furnace, heated to 900 °C at a rate of 5 °C / min, introduced with methane gas and a vacuum degree of 3 KPa, maintained for 16 h, and then naturally cooled to room temperature to obtain a carburized composite ceramic. 6) Grinding and polishing The carburized composite ceramics were ground with 600 mesh, 1200 mesh, 2000 mesh and 3000 mesh sandpaper in turn to remove the surface carbon layer, and finally polished until the surface roughness was less than 0.1 μm, thus completing the material preparation.

[0028] Example 3 In this embodiment, magnesium oxide is used as a stabilizer, aluminum oxide whiskers are used, and vacuum carburization is used to prepare zirconium oxide-based composite ceramics, with the total mass of the powder as a reference. The specific implementation includes the following steps: 1) Yttria-stabilized zirconia slurry 85 wt% of zirconium oxide powder, magnesium oxide stabilizer and anhydrous ethanol were added into a zirconium oxide ball mill, wherein the amount of magnesium oxide added was 3 mol% of zirconium oxide, the volume ratio of anhydrous ethanol to powder was 1-1.5, the ball mill speed was 200 r / min, the ball milling time was 10 h, and the grinding balls were filtered out to obtain a mixed slurry; 2) Composite powder preparation 10 wt% alumina whiskers were added to the mixed slurry, and the mixture was stirred for 90 min; the mixed slurry was then dried and sieved (mesh size 200) to obtain silicon carbide whisker reinforced zirconia composite powder; 3) Composite ceramic blank The composite powder was placed in a mold and kept at a static pressure of 300 MPa for 20 min to obtain a composite ceramic green body; 4) Composite ceramic firing The composite ceramic green body was placed in a vacuum sintering furnace, the furnace temperature was raised to 1450°C at a rate of 5°C / min, and after being kept at this temperature for 5 hours, it was naturally cooled to room temperature to obtain a composite ceramic. 5) Carburizing The composite ceramic was placed in a vacuum carburizing furnace, heated to 950 °C at a rate of 5 °C / min, ethylene gas was introduced, the vacuum degree was 1.5 KPa, and the temperature was maintained for 24 h before naturally cooling to room temperature to obtain a carburized composite ceramic. 6) Grinding and polishing The carburized composite ceramics were ground with 600 mesh, 1200 mesh, 2000 mesh and 3000 mesh sandpaper in turn to remove the surface carbon layer, and finally polished until the surface roughness was less than 0.1 μm, thus completing the material preparation.

[0029] Comparative Example 1 This comparative example is a yttria-stabilized zirconia ceramic, based on the total mass of the powder. Unlike the above-mentioned embodiment, whiskers are not added as a toughening phase and carburization treatment is not performed. The specific implementation includes the following steps: 1) Yttria-stabilized zirconia slurry 80 wt% of zirconium oxide powder, yttrium oxide stabilizer and anhydrous ethanol were added into a zirconium oxide ball mill, wherein the amount of yttrium oxide added was 3 mol% of zirconium oxide, the volume ratio of anhydrous ethanol to powder was 1-1.5, the ball mill speed was 200 r / min, the ball milling time was 10 h, and the grinding balls were filtered out to obtain a mixed slurry; 2) Powder preparation Adding polyvinyl alcohol to the mixed slurry for granulation, drying, and sieving (mesh number 200) to obtain yttria-stabilized zirconia powder; 3) Ceramic blank The composite powder was placed in a mold and kept at a static pressure of 300 MPa for 20 min to obtain a zirconia ceramic blank; 4) Ceramic firing The zirconia ceramic blank was placed in a vacuum sintering furnace, the furnace temperature was increased to 1450°C at a rate of 5°C / min, and then naturally cooled to room temperature after being kept for 2 h to obtain yttria-stabilized zirconia ceramics.

[0030] 5) Grinding and polishing The zirconia ceramic is ground and polished until the surface roughness is less than 0.1 μm, and the material preparation is completed.

[0031] Comparative Example 2 The comparative example is a silicon carbide whisker toughened zirconium oxide-based composite ceramic, based on the total mass of the powder. The specific implementation includes the following steps: 1) Yttria-stabilized zirconia slurry 80 wt% of zirconium oxide powder, yttrium oxide stabilizer and anhydrous ethanol were added into a zirconium oxide ball mill, wherein the amount of yttrium oxide added was 3 mol% of zirconium oxide, the volume ratio of anhydrous ethanol to powder was 1-1.5, the ball mill speed was 200 r / min, the ball milling time was 10 h, and the grinding balls were filtered out to obtain a mixed slurry; 2) Composite powder preparation 10 wt% silicon carbide whiskers and 0.75 wt% binder (PVB) were added to the mixed slurry, and the mixture was stirred for 90 min; the mixed slurry was then dried and sieved (mesh size 200) to obtain silicon carbide whisker reinforced zirconia composite powder; 3) Composite ceramic blank The composite powder was placed in a mold and kept at a static pressure of 300 MPa for 20 min to obtain a composite ceramic green body; 4) Composite ceramic firing The composite ceramic blank was placed in a vacuum sintering furnace, the furnace temperature was raised to 1450°C at a rate of 5°C / min, and after being kept at this temperature for 2.5 hours, it was naturally cooled to room temperature to obtain a composite ceramic blank; 5) Grinding and polishing The composite ceramic blank was ground with 600 mesh, 1200 mesh, 2000 mesh and 3000 mesh sandpaper in sequence, and finally polished until the surface roughness was less than 0.1 μm, thus completing the material preparation.

[0032] Comparative Example 3 This comparative example is a carburized yttria-stabilized zirconia ceramic, based on the total mass of the powder. Unlike the above-mentioned embodiment, whiskers are not added as a toughening phase, and the specific implementation includes the following steps: 1) Yttria-stabilized zirconia slurry 80 wt% of zirconium oxide powder, yttrium oxide stabilizer and anhydrous ethanol were added into a zirconium oxide ball mill, wherein the amount of yttrium oxide added was 3 mol% of zirconium oxide, the volume ratio of anhydrous ethanol to powder was 1-1.5, the ball mill speed was 200 r / min, the ball milling time was 10 h, and the grinding balls were filtered out to obtain a mixed slurry; 2) Powder preparation Adding polyvinyl alcohol to the mixed slurry for granulation, drying, and sieving (mesh number 200) to obtain yttria-stabilized zirconia powder; 3) Ceramic blank The yttria-stabilized zirconia was placed into a mold and maintained at a static pressure of 300 MPa for 20 min to obtain a yttria-stabilized zirconia ceramic blank; 4) Ceramic firing The zirconia ceramic blank was placed in a vacuum sintering furnace, the furnace temperature was increased to 1450°C at a rate of 5°C / min, and then naturally cooled to room temperature after being kept for 2 h to obtain yttria-stabilized zirconia ceramics.

[0033] 5) Carburizing The composite ceramic was placed in a vacuum carburizing furnace, heated to 900 °C at a rate of 5 °C / min, introduced with acetylene gas and a vacuum degree of 2 KPa, maintained for 20 h, and then naturally cooled to room temperature to obtain a carburized yttria-stabilized zirconia ceramic blank; 6) Grinding and polishing The carburized yttria-stabilized zirconia ceramics were ground with 600-mesh, 1200-mesh, 2000-mesh and 3000-mesh sandpapers in sequence to remove the surface carbon layer, and finally polished until the surface roughness was less than 0.1 μm, thus completing the material preparation.

[0034] Figure 1 A schematic diagram showing the structure of the vacuum high wear-resistant zirconia-based composite ceramic material of the present invention.

[0035] Figure 2 The physical pictures of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown for comparison. It can be seen that the composite ceramic material prepared by the method of the present invention is gray-black, Comparative Example 1 and Comparative Example 2 are white, and Comparative Example 3 is dark gray-black.

[0036] Figure 3 The fracture toughness test results of the ceramic materials prepared in the examples and comparative examples are shown. The test was performed using a Vickers microhardness tester and a light microscope, and the test load was consistent with 49 N. The results show that the fracture toughness of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 are 11.4 MPa·m 1 / 2 , 10.6 MPa·m 1 / 2 、11.75 MPa·m 1 / 2 and 7.85 MPa·m 1 / 2 It can be seen that Example 1 and Comparative Example 2 have similar high fracture toughness, while single carburization will lead to a decrease in fracture toughness of about 20%-30%.

[0037] Figure 4 As shown in the figure, the average friction coefficient and wear rate of the embodiment and the comparative example are compared under the same pairing and test parameters. -4 Under the conditions of Pa environment, zirconia pair (Ø6 mm), and 4 N normal load, the wear rate of Example 1 is 3.0×10 -7 mm 3 / N·m, the average wear rate of comparative example 1 is 9.9×10 -6 mm 3 / N·m, the average wear rate of comparative example 2 is 8.45×10-6 mm 3 / N·m, the average wear rate of comparative example 3 is 2.12×10 -6 mm 3 / N·m. The wear rate of Example 1 is approximately 1 / 33, 1 / 27 and 1 / 7 of that of Comparative Examples 1, 2 and 3, indicating that simple whisker toughening cannot significantly improve the wear resistance of zirconia ceramics in vacuum, and Example 1 obviously has better vacuum wear resistance.

[0038] In summary, the method disclosed in the present invention combines whisker toughening with carburizing to prepare a zirconia-based composite ceramic material with excellent vacuum wear resistance. The material is mainly composed of zirconia, stabilizer, toughening whiskers, and a carburized layer for improving tribological properties, wherein: the stabilizer is one or more of yttrium oxide, magnesium oxide, and calcium oxide, the toughening whiskers are one or more of high-temperature resistant silicon carbide, silicon nitride, aluminum oxide, and magnesium oxide, and the carburized layer is formed by vacuum high-temperature carburizing treatment. The present invention proposes that its vacuum wear resistance is 1-2 orders of magnitude higher than that of traditional yttrium oxide or magnesium oxide stabilized zirconia materials, providing a new type of high-wear-resistant composite ceramic material for high-end equipment components in the aerospace field.

[0039] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a vacuum high wear-resistant zirconia-based composite ceramic material, characterized in that: The following steps are involved: 1) Fully mix zirconium oxide powder, stabilizer and anhydrous ethanol to prepare a mixed slurry; 2) Add whiskers to the mixed slurry, stir thoroughly, and then dry and sieve to obtain a mixed powder; 3) The mixed powder is statically pressed to obtain a composite ceramic green body, and then vacuum sintered and annealed to obtain a composite ceramic; 4) Carburizing the composite ceramic at high temperature to obtain carburized composite ceramic, and then subjecting the composite ceramic to surface treatment to obtain a vacuum high wear-resistant zirconia-based composite ceramic material.

2. The method for preparing a vacuum high wear-resistant zirconia-based composite ceramic material according to claim 1, characterized in that: In step 1), the amount of stabilizer is 1.5% to 5% of the amount of zirconium oxide powder; the volume ratio of the total powder of zirconium oxide powder and stabilizer to anhydrous ethanol is 1 to 1.5:

1.

3. The method for preparing a vacuum high wear-resistant zirconia-based composite ceramic material according to claim 1, characterized in that: The stabilizer is one or more of yttrium oxide, magnesium oxide and calcium oxide.

4. The method for preparing a vacuum high wear-resistant zirconia-based composite ceramic material according to claim 1, characterized in that: In step 2), the amount of whiskers used accounts for 5% to 20% of the mass of the mixed slurry; the whiskers are one or more of silicon carbide, silicon nitride, aluminum oxide and magnesium oxide.

5. The method for preparing a vacuum high wear-resistant zirconia-based composite ceramic material according to claim 1, characterized in that: In step 3), the static pressing pressure is 150 MPa~300 MPa, and the holding time is 10 min~30 min; the process parameters of vacuum sintering and annealing treatment are: starting from room temperature, the temperature is increased to 1200 ℃-1500 ℃ at a temperature rise rate of 3~10 ℃ / min, the holding time is 2 h~10 h, and then cooled to room temperature with the furnace.

6. The method for preparing a vacuum high wear-resistant zirconia-based composite ceramic material according to claim 1, characterized in that: In step 4), the process parameters of high temperature carburizing treatment are: the carburizing medium is one or more of methane, ethane, acetylene and ethylene, the temperature is increased from room temperature to 850 ℃ ~ 1450 ℃ at a temperature rise rate of 3 ~ 10 ℃ / min, the carburizing time is 8 h ~ 24 h, and the cavity pressure is 1 ~ 20 KPa.

7. The method for preparing a vacuum high wear-resistant zirconia-based composite ceramic material according to claim 1, characterized in that: In step 5), the surface is treated by grinding and polishing with 600 mesh, 1200 mesh, 2000 mesh and 3000 mesh sandpaper in sequence until the surface roughness is less than 0.1 μm.

8. A vacuum high wear-resistant zirconia-based composite ceramic material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The vacuum high wear-resistant zirconia-based composite ceramic material contains a carburized layer inside and is distributed with whiskers as a toughening phase.

9. The vacuum high wear-resistant zirconia-based composite ceramic material according to claim 8, characterized in that: The thickness of the carburized layer with a carbon content higher than 0.75% is greater than 10 μm; the length of the whiskers is 5 μm to 150 μm, and the aspect ratio is greater than 5; The dry friction wear rate of the vacuum high wear-resistant zirconia-based composite ceramic material in a vacuum environment is 10 -7 ~10 -8 mm 3 / N·m order of magnitude.

10. Application of the vacuum high wear-resistant zirconia-based composite ceramic material according to claim 8 or 9 in the field of aerospace high-end equipment manufacturing.

Citation Information

Patent Citations

  • Carburizing method for oxide ceramic

    CN103724051A

  • Production method of whisker type toughened ceramic

    CN106542839A

  • Cooling and accelerating vacuum carburizing method

    CN110042339A

  • Method for carburizing ceramic sliding material

    CN1108229A

  • Preparation method of sintered high-density zirconium dioxide ceramic for sliding plate brick

    CN112110749A

Cited By

  • Gradient alumina-based grinding ball based on shape regulation and control, preparation method and scrap recycling method of grinding ball

    CN121627388A

  • A gradient alumina-based grinding ball based on shape-modulated properties, its preparation method, and its recycling method after disposal.

    CN121627388B